Zur Eröffnung des Carl Friedrich von Weizsäcker-Zentrums für Naturwissenschaft und Friedensforschung - Kalinowski, Martin B.; Spitzer, Hartwig (Hamburger Universitätsreden Neue Folge, 2007)
This volume documents the speeches given on July 7, 2006 in Hamburg on the occasion of the ceremonial opening of the Carl Friedrich von Weizsäcker Center for Science and Peace Research (Zentrum für Naturwissenschaft und Friedensforschung, ZNF). The keynote speakers were Alyson J. K. Bailes, Head of the Stockholm Peace Research Institute (SIPRI), former Minister of State, Prof. Egon Bahr, former Head of the Hamburg Peace Research Institute (scientific peace research has gained a unique institutional foothold in Germany. Together with the Institut für Friedensforschung und Sicherheitpolitik, IFSH), Prof. Ernst Ulrich von Weizsäcker, a son of the namesake of the ZNF, and Prof. Wolfgang Panofsky from Stanford, USA.With the founding of the Centre at the University of Hamburg, headed by Prof. Dr. Martin Kalinowski, scientific peace research has gained a unique institutional foothold in Germany. Together with the IFSH in Hamburg an inter- and multidisciplinary research network is being established which will open up new opportunities to explore the interaction of natural sciences, conflicts and international security against the background of the guiding principles of peace and sustainability and to integrate them into the training of natural scientists.